‘Florida Radiance’ Strawberry - Vance M. Whitaker; Craig K. Chandler; Bielinski M. Santos; Natalia A. Peres (EDIS, 2013)
‘Florida Radiance’ is a strawberry cultivar released from UF/IFAS in 2008. As of 2012, it has become a major cultivar in Florida and other winter and early spring production regions worldwide. In all markets outside the United States and Canada, it is marketed as ‘Florida Fortuna’. In addition to commercial production, it has been tested for many years in field plots at the UF/IFAS Gulf Coast Research and Education Center in Wimauma and the Florida Strawberry Growers Association headquarters in Dover for disease, fruit, and plant traits. This 4-page fact sheet was written by Vance M. Whitaker, Craig K. Chandler, Bielinski M. Santos, and Natalia A. Peres, and published by the UF Department of Horticultural Sciences, June 2013.